2012
DOI: 10.1002/ppul.22709
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory muscle function in patients with cystic fibrosis

Abstract: Respiratory muscle function in patients with cystic fibrosis (CF) can be assessed by measurement of maximal inspiratory pressure (Pimax ), maximal expiratory pressure (Pemax ), and pressure-time index of the respiratory muscles (PTImus ). We investigated the differences in maximal respiratory pressures and PTImus between CF patients with no gross hyperinflation and healthy controls and described the effects of pulmonary function and nutrition impairment on respiratory muscle function in this group of CF patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 28 publications
(48 reference statements)
3
34
0
Order By: Relevance
“…Differences between the two study groups or between younger (7-11-y old) and older participants (12-34-y old) were tested for significance using the Mann-Witney rank sum test or χ 2 test, as appropriate. Since younger children have significantly different respiratory muscle function than older children and young adults (9), a general linear model was applied to evaluate the possible effect of: (i) health status (CF diagnosis vs. non-CF); (ii) age group (7-11 y of age vs. 12-34 y of age); and (iii) the interaction of health status with age, on τ. Kendall-tau rank correlation coefficient was used to examine the relationship of τ with BMI z-score, UAMA, RR, and TV in both patients with CF and control participants. For CF patients only, the correlations of τ with FVC z-score, FEV 1 z-score, and FEF z-score were also assessed.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Differences between the two study groups or between younger (7-11-y old) and older participants (12-34-y old) were tested for significance using the Mann-Witney rank sum test or χ 2 test, as appropriate. Since younger children have significantly different respiratory muscle function than older children and young adults (9), a general linear model was applied to evaluate the possible effect of: (i) health status (CF diagnosis vs. non-CF); (ii) age group (7-11 y of age vs. 12-34 y of age); and (iii) the interaction of health status with age, on τ. Kendall-tau rank correlation coefficient was used to examine the relationship of τ with BMI z-score, UAMA, RR, and TV in both patients with CF and control participants. For CF patients only, the correlations of τ with FVC z-score, FEV 1 z-score, and FEF z-score were also assessed.…”
Section: Discussionmentioning
confidence: 99%
“…surface diaphragmatic electromyography can be affected appreciably by electrical "noise" from neighboring or underlying muscle groups or by levels of subcutaneous fat. Moreover, the noninvasive tension-time index of the respiratory muscles has been explored in CF patients in a number of studies and high values of TT mus have been reported, also indicating an increased risk of inspiratory muscle fatigue and respiratory failure (2,3,9). Unfortunately, measurement of the tensiontime index requires the utilization of pneumotachograph and differential-pressure transducers, i.e., a technical setup which is only found in specialized research laboratories.…”
Section: Inspiratory Muscle Relaxation In Cf Articlesmentioning
confidence: 99%
See 3 more Smart Citations